2014
DOI: 10.1002/2014gc005269
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic structure, lithology, and hydrothermal signature of the Rainbow massif (Mid-Atlantic Ridge 36°14′N)

Abstract: Rainbow is a dome-shaped massif at the 36 14 0 N nontransform offset along the Mid-AtlanticRidge. It hosts three ultramafic-hosted hydrothermal sites: Rainbow is active and high temperature; Clamstone and Ghost City are fossil and low temperature. The MoMARDREAM cruises (2007, 2008) presented here provided extensive rock sampling throughout the massif that constrains the geological setting of hydrothermal activity. The lithology is heterogeneous with abundant serpentinites surrounding gabbros, troctolites, ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 104 publications
(207 reference statements)
1
94
1
Order By: Relevance
“…Along with these changes, the major faults that bound the axial valleys increase in throw and lateral separation approaching the NTD, culminating in core complex formation at the NTD itself. The now‐inactive detachment fault at Rainbow is thought to be located on the western side of the massif, where bathymetry data show a clear break in slope between the massif and the neighbor valley floor (e.g., Andreani et al, ). Consistent with that location, seismic reflection images from the MARINER experiment show evidence for the detachment from an unconformity of flat reflectors against material with a different reflectivity structure (Figure a).…”
Section: Discussionmentioning
confidence: 99%
“…Along with these changes, the major faults that bound the axial valleys increase in throw and lateral separation approaching the NTD, culminating in core complex formation at the NTD itself. The now‐inactive detachment fault at Rainbow is thought to be located on the western side of the massif, where bathymetry data show a clear break in slope between the massif and the neighbor valley floor (e.g., Andreani et al, ). Consistent with that location, seismic reflection images from the MARINER experiment show evidence for the detachment from an unconformity of flat reflectors against material with a different reflectivity structure (Figure a).…”
Section: Discussionmentioning
confidence: 99%
“…Hydrothermal systems hosted by this formation could be related to the alteration of the gabbroic core and/or serpentinization of interfingered ultramafic formations (Andreani et al, 2014;McCaig et al, 2010;Blackman et al, 2014). The origin and extent of possible hydrothermal circulation processes in the subsurface of OCCs and their exact fluid pathways have been discussed extensively in previous studies; yet, the direct evidence remains very sparse except for fluid seepage found from seafloor observations (Andreani et al, 2014;Delacour et al, 2008aDelacour et al, , 2008bEscartín et al, 2008;Früh-Green et al, 2003;Karson et al, 2006;Kelley et al, 2001Kelley et al, , 2005Ludwig et al, 2006Ludwig et al, , 2011Macleod et al, 2011;Tucholke et al, 2013). It has been observed that nearly all ultramafic and gabbroic rocks recovered from the upper 800 m of IODP Hole U1309D on the Central Dome, located in close proximity to our prevalent lithified carbonate crust at Argo II track A39 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Asymmetric spreading, where one flank exhibits detachment faulting, is estimated to occur along approximately 50% of the Mid-Atlantic Ridge (MAR) axis (Escartín et al, 2008). Since their discovery, OCC exposures have provided information on the formation and evolution of the slow-spreading axial environment, including detachment faulting (Blackman et al, 1998(Blackman et al, , 2002(Blackman et al, , 2011Dick et al, 2008;Canales et al, 2008;Henig et al, 2012;MacLeod et al, 2009;Mallows and Searle, 2012;Morris et al, 2009;Schroeder and John, 2004;Tucholke et al, 1998Tucholke et al, , 2001, subsurface fluid flow and associated serpentinization processes (Andreani et al, 2014;Blackman et al, 2002Blackman et al, , 2011Delacour et al, 2008aDelacour et al, , 2008bFrüh-Green et al, 2003Karson et al, 2006;Kelley et al, 2001;McCaig et al, 2010;Schroeder et al, 2002;Tucholke et al, 2013), and the accompanying biogeochemical activities (Andreani et al, 2014;Früh-Green et al, 2003Karson et al, 2006;Kelley et al, 2001Kelley et al, , 2005Schroeder et al, 2002;Tucholke et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Many seafloor massive sulfides in the recent oceans, including the largest and those with the highest Cu grade (Petersen and Hein, 2013;Hein et al, 2013), are hosted in the peridotite-dominated lithosphere with a thin and heterogeneous crust (Gràcia et al, 2000;Kelley et al, 2001;Petersen et al, 2009;Pertsev et al, 2012;Kostitsyn et al, 2013;Tucholke et al, 2013;Andreani et al, 2014;Ciazela et al, 2015), where melt-mantle reaction is likely more enhanced (Ciazela et al, 2017b). In on-land prospecting, the search for chalcophile deposits seeks regions with both an appropriately enriched source rock, and a mechanism for concentrating those elements in a deposit.…”
Section: Crust-mantle Transition Zones and Related Sulfide Ore Depositsmentioning
confidence: 99%